Negative Regulation of Abscisic Acid Signaling by the Fagus sylvatica FsPP2C1 Plays A Role in Seed Dormancy Regulation and Promotion of Seed Germination - González-García, Mary Paz (The American Society for Plant Biologists, 2003)
FsPP2C1 was previously isolated from beech (Fagus sylvatica) seeds as a functional protein phosphatase type-2C (PP2C) with all the conserved features of these enzymes and high homology to ABI1, ABI2, and PP2CA, PP2Cs identified as negative regulators of ABA signaling. The expression of FsPP2C1 was induced upon abscisic acid (ABA) treatment and was also up-regulated during early weeks of stratification. Furthermore, this gene was specifically expressed in ABA-treated seeds and was hardly detectable in vegetative tissues. In this report, to provide genetic evidence on FsPP2C1 function in seed dormancy and germination, we used an overexpression approach in Arabidopsis because transgenic work is not feasible in beech. Constitutive expression of FsPP2C1 under the cauliflower mosaic virus 35S promoter confers ABA insensitivity in Arabidopsis seeds and, consequently, a reduced degree of seed dormancy. Additionally, transgenic 35S:FsPP2C1 plants are able to germinate under unfavorable conditions, as inhibitory concentrations of mannitol, NaCl, or paclobutrazol. In vegetative tissues, Arabidopsis FsPP2C1 transgenic plants show ABA-resistant early root growth and diminished induction of the ABA-response genes RAB18 and KIN2, but no effect on stomatal closure regulation. Seed and vegetative phenotypes of Arabidopsis 35S:FsPP2C1 plants suggest that FsPP2C1 negatively regulates ABA signaling. The ABA inducibility of FsPP2C1 expression, together with the transcript accumulation mainly in seeds, suggest that it could play an important role modulating ABA signaling in beechnuts through a negative feedback loop. Finally, we suggest that negative regulation of ABA signaling by FsPP2C1 is a factor contributing to promote the transition from seed dormancy to germination during early weeks of stratification.